Social discourse in the power of distance learning implementation during the Covid-19 pandemic - Putri Dwi Permata Indah (Jurnal Sosiologi Dialektika, 2022)
The Covid-19 pandemic has had an impact on various sectors including changes in the learning process in schools. As an important component in education, teachers have a role in supporting teaching and learning activities during the Covid-19 pandemic. However, teachers in implementing distance learning face obstacles in the form of unpreparedness to adapt to the technology used. This problem is also experienced by teachers at SDN Jajar Tunggal 1 Surabaya, so teachers must force themselves to continue learning using technology. This study aims to determine the discourse created in the implementation of distance learning. The method used in this study is a qualitative research method with Michael Foucault’s genealogical approach, and the determination of informants is carried out purposively. The results of this study are teachers have different discourses in seeing the implementation of distance learning. The implementation of distance learning using Microsoft Office 365 is used as a form of discipline for teachers. The use of technology makes it easier for schools and related agencies to evaluate teachers by standardizing the ability of teachers to apply technology. This study concludes that teachers have different discourses in the implementation of distance learning which are influenced by the knowledge of each teacher.